Representações de gênero em Vira-Vira, Violeta - Porto Diniz, Rozeane; Karlo-Gomes, Geam (Revista Estudos Feministas, 2020)
LACERDA, Socorro. Vira-vira, Violeta. Petrolina, PE: Edição da Autora, 2017.